Candida guilliermondii Complex Is Characterized by High Antifungal Resistance but Low Mortality in 22 Cases of Candidemia - Marcos-Zambrano, Laura Judith (Antimicrob Agents Chemother, 2017)
The objectives of our study were to describe the characteristics of patients with Candida guilliermondii candidemia and to perform an in-depth microbiological characterization of isolates and compare them with those of patients with C. albicans candidemia. We described the risk factors and outcomes of 22 patients with candidemia caused by the C. guilliermondii complex. Incident isolates were identified using molecular techniques, and susceptibility to fluconazole, anidulafungin, and micafungin was studied. Biofilm formation was measured using the crystal violet assay (biomass production) and the XTT reduction assay (metabolic activity), and virulence was studied using the Galleria mellonella model. Biofilm formation was compared with that observed for C. albicans. The main conditions predisposing to infection were malignancy (68%), immunosuppressive therapy (59%), and neutropenia (18%). Clinical presentation of candidemia was less severe in patients infected by the C. guilliermondii complex than in patients infected by C. albicans, and 30-day mortality was lower in C. guilliermondii patients (13.6% versus 33.9%, respectively; P = 0.049). Isolates were identified as C. guilliermondii sensu stricto (n = 17) and Candida fermentati (n = 5). The isolates produced biofilms with low metabolic activity and moderate biomass. The G. mellonella model showed that C. guilliermondii was less virulent than C. albicans (mean of 6 days versus 1 day of survival, respectively; P < 0.001). Patients with candidemia caused by the C. guilliermondii complex had severe and debilitating underlying conditions. Overall, the isolates showed diminished susceptibility to fluconazole and echinocandins, although poor biofilm formation and the low virulence were associated with a favorable outcome.